Benjamin F. Whitten papers - Whitten, Benjamin F. (Benjamin Franklin), approximately 1836-
Correspondence, family papers, military records, financial and legal records, and other papers relating primarily to Whitten's Civil War service with the 9th Maine Infantry Regiment. Documents his participation in the Battle of Morris Island, S.C., 1863; other actions and encampments along the southeast Atlantic coast in 1862 and 1863; the Battle of Cold Harbor, Va., 1864; and engagements in Bermuda Hundred, Va., where he was taken captive as a prisoner of war. Subjects include music, education, and the recruitment and performance of African American soldiers, especially those serving in the 54th Massachusetts Infantry Regiment; and community life among former slaves in the South. Includes correspondence between Whitten and his wife, Abigail, concerning homesteading in Nebraska and other personal matters. Also includes correspondence of other Whitten family members and of American servicemen during World War I and World War II.
Union Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Whitten, Abigail -- Correspondence; Whitten family; United States. -- Army. -- Maine Infantry Regiment, 9th (1861-1865); United States. -- Army. -- Massachusetts Infantry Regiment, 54th (1863-1865); African Americans -- Education; Cold Harbor, Battle of, Va., 1864.; Freedmen -- Southern States -- Social life and customs; Frontier and pioneer life -- Nebraska; Morris Island, Battle of, S.C., 1863 (July 10-September 7); World War, 1914-1918.; World War, 1939-1945.; Bermuda Hundred Region (Va.) -- History -- Civil War, 1861-1865.; Fort Wagner (S.C.); South Atlantic States -- History -- Civil War, 1861-1865 -- Campaigns; South Carolina -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- African Americans; United States -- History -- Civil War, 1861-1865 -- Participation, African American; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865 -- Songs and music; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Army officers